Temporal Trends in Complex Percutaneous Coronary Interventions - Kheifets, Mark; Vons, Shelly Abigail; Bental, Tamir; Vaknin-Assa, Hana; Greenberg, Gabriel; Samara, Abed; Codner, Pablo; Wittberg, Guy; Talmor Barkan, Yeela; Perl, Leor; Kornowski, Ran; Levi, Amos (Frontiers in Cardiovascular Medicine, 2022)
Background Accumulated experience combined with technological advancements in percutaneous coronary interventions (PCI) over the past four decades, has led to a gradual increase in PCI utilization and complexity. We aimed to investigate the temporal trends in PCI complexity and the outcomes of complex PCI (C-PCI) in our institution. Methods We analyzed 20,301 consecutive PCI procedures performed over a 12-year period. C-PCI was defined as a procedure involving at least one of the following: Chronic total occlusion (CTO), left main (LM), bifurcation or saphenous vein graft (SVG) PCI. Four periods of 3-year time intervals were defined (2008–10, 2011–2013, 2014–2016, 2017–2019), and temporal trends in the rate and outcomes of C-PCI within these intervals were studied. Endpoints included mortality and major adverse cardiac events [MACE: death, acute myocardial infarction (MI), and target vessel revascularization (TVR)] at 1 year. Results A total of 5,647 (27.8%) C-PCI procedures were performed. The rate of C-PCI has risen significantly since 2,017 (31.2%, p < 0.01), driven mainly by bifurcation and LM interventions (p < 0.01). At 1-year, rates of death, acute MI, TVR and MACE, were all significantly higher in the C-PCI group (8.8 vs. 5.1%, 5.6 vs. 4.5%, 5.5 vs. 4.0%, 17.2 vs. 12.2%, p < 0.001 for all, respectively), as compared to the non-complex group. C-PCI preformed in the latter half of the study period (2014–2019) were associated with improved 1-year TVR (4.4% and 4.8% vs. 6.7% and 7.1%, p = 0.01, respectively) and MACE (13.8% and 13.5% vs. 17.3% and 18.2%, p = 0.001, respectively) rates compared to the earlier period (2007–2013). Death rate had not significantly declined with time. Conclusion In the current cohort, we have detected a temporal increase in PCI complexity coupled with improved 1-year clinical outcomes in C-PCI.